Pengaruh Harga dan Kualitas Pelayanan terhadap Loyalitas Konsumen Rumah Makan Padang, Jl. Tuasan No.194 - Zainarti; Sasmita Pohan; Aprilia Regitasya Parinduri; Ardiansyah Dalimunthe; Alhabib Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of price and service quality on consumer loyalty at the Padang Restaurant located at Jl. Tuasan No. 194. A quantitative approach was employed using questionnaires distributed to 100 respondents selected through accidental sampling. Data were analyzed using multiple linear regression, including t-tests, F-tests, and coefficient of determination. The results show that price has a positive and significant effect on consumer loyalty. Service quality also has a positive and significant effect. Simultaneously, both variables contribute strongly to shaping consumer loyalty. These findings indicate that the combination of appropriate pricing strategies and consistent service quality can enhance consumers’ intentions to revisit and recommend the restaurant to others.